2021
DOI: 10.1542/peds.2021-052904
|View full text |Cite
|
Sign up to set email alerts
|

National Pediatric Experience With Virtual Interviews: Lessons Learned and Future Recommendations

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Few studies have identified specific advantages and barriers to the virtual interview format. 7,8,14,16,20,21,34 Our findings identified cost savings and time efficiency as significant advantages,in line with other studies. Novel to our study, carbon footprint savings was the secondmost selected advantage.…”
Section: Discussionsupporting
confidence: 90%
“…Few studies have identified specific advantages and barriers to the virtual interview format. 7,8,14,16,20,21,34 Our findings identified cost savings and time efficiency as significant advantages,in line with other studies. Novel to our study, carbon footprint savings was the secondmost selected advantage.…”
Section: Discussionsupporting
confidence: 90%
“…APPD also recommended that programs interview all applicants virtually, even local applicants, and programs consider how to market themselves to applicants. 24 …”
Section: Changes In Program Recruitmentmentioning
confidence: 99%
“…Over half of all residency programs (n = 138) participated in the webinar series, with several hundred applicants attending each session. 24 …”
Section: Changes In Program Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Residency programs have collectively struggled to find the best approach to interview virtually in a manner that allows adequate applicant assessment while ensuring accurate representation of their program's offerings. 4 Huppert et al reviewed the limited data on virtual interviews in order to clarify best practices. 5 Their recommendations included having a detailed interview plan, using standardized questions, preparation of current residents as hosts for virtual interviews, the development of electronic materials for the program including virtual social events, and the collection and analysis of data regarding each program's interview process.…”
mentioning
confidence: 99%